The role of consumer satisfaction in mediating product quality and online service quality on repeat product purchase decisions - Thejaya, Goldina; Antonio, Tony (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
This research aims to determine the influence of product quality and online service quality on consumer satisfaction and repeat product purchase decisions in an online pastry business. This research uses a quantitative approach with a sample of 51 consumers who have made purchases more than twice in a period of 6 months. The results show that product quality and online service quality have a significant effect on consumer satisfaction, which in turn has a significant effect on repeat purchase decisions. This research is expected to provide insight and strategic recommendations in improving product quality and online service quality, thus increasing consumer satisfaction and encouraging repeat purchase decisions. The research results will also contribute to marketing and business literature by deepening understanding of the relationship between product quality and online service quality, consumer satisfaction, and repeat purchase decisions in the context of online business in Indonesia.